Upaya Peningkatan Hasil Belajar Siswa Melalui Penggunaan Metode Eksperimen pada Mata Pelajaran IPA Siswa Kelas V UPTD SDN 4 Adirejo - Dharma, Adimas Surya; Fitriani, Silvia (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
This research aims to improve student learning outcomes in science learning and heat transfer materials through the use of experimental methods. The research consisted of pre-cycle, cycle I and cycle II with the subject being class V students consisting of 15 students. By looking at the acquisition data and findings, it can be seen that the teacher has implemented learning improvement activities. Using the Experimental Method can improve student learning outcomes, this can be seen by increasing the percentage of student completion in each cycle. Pre-Cycle with a percentage of students completing (27%) Cycle II (70%) and Cycle II (87%). There was a significant increase in student learning outcomes after using the Experimental Method in class V science subjects on heat transfer material at UPTD SDN 4 Adirejo